2019
DOI: 10.1101/729731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-scale biophysical determinants of cell competition in epithelia

Abstract: How cells with different genetic makeups compete in tissues is an outstanding question in developmental biology and cancer research. Studies in recent years have revealed two fundamental mechanisms of cell competition, driven by short-range biochemical signalling or by long-range mechanical stresses within the tissue. In both scenarios, the outcome of cell competition has generally been characterised using population-scale metrics. However, the underlying strategies for competitive interactions at the single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…As reported before, we confirmed that, when cocultured with wild-type (WT) cells, GFP-expressing scrib KD cells were outcompeted by cell competition in a tetracycline (Tet)-dependent manner (Figure S1A). [7][8][9][10] We also observed that the density of scrib KD cells was remarkably increased after tetracycline addition compared to that of WT cells in cell competition, suggesting that scrib KD cells were compacted (Figure S1B). [7][8][9] A previous report showed that, when WT and scrib KD colonies come into contact, both colonies move synchronously, with scrib KD colony always followed by WT colony, suggesting that this migratory behavior promotes the compression and elimination of scrib KD cells in cell competition.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…As reported before, we confirmed that, when cocultured with wild-type (WT) cells, GFP-expressing scrib KD cells were outcompeted by cell competition in a tetracycline (Tet)-dependent manner (Figure S1A). [7][8][9][10] We also observed that the density of scrib KD cells was remarkably increased after tetracycline addition compared to that of WT cells in cell competition, suggesting that scrib KD cells were compacted (Figure S1B). [7][8][9] A previous report showed that, when WT and scrib KD colonies come into contact, both colonies move synchronously, with scrib KD colony always followed by WT colony, suggesting that this migratory behavior promotes the compression and elimination of scrib KD cells in cell competition.…”
mentioning
confidence: 69%
“…[7][8][9][10] We also observed that the density of scrib KD cells was remarkably increased after tetracycline addition compared to that of WT cells in cell competition, suggesting that scrib KD cells were compacted (Figure S1B). [7][8][9] A previous report showed that, when WT and scrib KD colonies come into contact, both colonies move synchronously, with scrib KD colony always followed by WT colony, suggesting that this migratory behavior promotes the compression and elimination of scrib KD cells in cell competition. 7 However, the precise mechanism by which the migratory behavior of WT and scrib KD colonies is induced remains unelucidated.…”
mentioning
confidence: 69%
“…Looking to previous work, mathematical modeling has played a critical role in understanding the evolutionary pressures that drive clonal competition in cancer ( Gatenby and Vincent, 2003 ; Vermeulen et al, 2013 ). Indeed, computational approaches using live-cell imaging data have been successful at disentangling cellular factors involved in 2-dimensional mechanical competition ( Gradeci et al, 2019 ). Additionally, modeling of intestinal stem cell clonality over time initially predicted that the progressive clonal takeover of intestinal crypts fit well with a stochastic model, indicating that neutral drift was the driver of clonality in non-oncogenic situations ( Snippert et al, 2010 ).…”
Section: Clonality and Competitionmentioning
confidence: 99%
“…This competition between losers and winners is essential for tissue homeostasis but it also emerges during tissue development and can play a role in various pathologies including tumor development ( Meyer et al, 2014 ; Moreno et al, 2019 ). Although the chemical signals driving the battle between two different cell populations are relatively more explored, an increasing number of studies showcases that mechanical signals such as differential sensitivity to compression during cell crowding are also crucial in driving such interactions ( Gradeci et al, 2019 ; Matamoro-Vidal and Levayer, 2019 ; Moreno et al, 2019 ; Bastounis et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%